First Appraisal of Effective Microplastics Removal from the Textile Manufacturing Processes - Estefanía Bonnail; Sebastián Vera; Julián Blasco; T. Ángel DelValls (Applied Sciences, 2025)
The textile industry consumes large volumes of freshwater, producing enormous wastewater containing chemicals from dyeing and bathing, but also microplastics concentrations that have not been deeply studied. Liquid wastes from the synthetic and natural textile manufacturers were treated with a new disruptive technology (Adiabatic Sonic Evaporation and Crystallization, ASEC), which completely removed contaminants from water, providing distilled water and crystallized solids. The current study presents the characterization of the industrial residues and the obtained by-products: microplastics and organic matter contained in the solid residue were analyzed and characterized through chromatography. The results of the analyses displayed that compounds such as benzene, benzoic acid and 2,4-dymethyl-1-heptene were found in the synthetic industry water samples as degraded compounds of polyester and polypropylene. Meanwhile, the natural industry water also contained polyester, nylon and PMM polymer. After the depuration of samples, microplastics were completely retained in the solid phase, together with the organic matter (sulfate and surfactants) resulting on clean water. This is the first study focused on the study of microplastics generated by the textile industry and their prevention by removing them as solid waste.